Preparation method of environment-friendly positive plate and lithium ion battery

By using a cathode slurry composed of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and lithium cobalt fully recovered positive electrode active materials, the existing cathode adhesives have health hazards and degraded bonding performance, and a lithium-ion battery with high energy density and stable circulation performance is achieved.

CN119542340APending Publication Date: 2025-02-28SICHUAN VOCATIONAL & TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411662690.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The positive electrode adhesives of existing lithium-ion batteries such as polyvinylidene fluoride (PVDF) are harmful to human health, expensive and degraded bonding performance, which affects the battery's circulation performance and energy density.

Method used

The positive electrode slurry composed of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and lithium cobalt fully recovered positive electrode active materials is used to improve the bonding strength and electron transport capability by forming a three-dimensional three-dimensional conductive network and hydrogen bonding force.

Benefits of technology

Effectively reduce the amount of adhesive used, increase the load of active substances, improve the energy density and circulation performance of the battery, and ensure the overall performance of the positive electrode sheet and lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542340A_ABST
    Figure CN119542340A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an environment-friendly positive plate, and relates to the field of lithium ion batteries, and the preparation method comprises the following steps: adding polyacrylonitrile into an NMP solvent to prepare an adhesive; adding conductive carbon nanotubes into an adhesive, then adding conductive carbon black into the solution, and finally adding a positive electrode active material into the solution to obtain positive electrode slurry; and uniformly coating two surfaces of the positive electrode slurry on a positive electrode current collector, and sequentially drying and rolling to obtain the positive electrode plate. In the preparation process of the positive plate, a non-toxic and harmless adhesive is adopted, the environmental protection requirement is met, the use amount of the adhesive can be effectively reduced, the loading amount of an active substance in an electrode is improved, the energy density of the battery is improved, and the performance of the lithium ion battery is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing an environmentally friendly positive electrode sheet and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in new energy vehicles, grid energy storage, portable electronic devices and other fields due to their high energy density, good cycle performance, and no memory effect. However, with the popularity of lithium-ion batteries, people have begun to pay attention to their corresponding environmental protection and safety issues. On the one hand, in the process of manufacturing lithium-ion batteries, raw materials that are harmless to human health need to be used. For example, the Regulation on Registration, Evaluation, Authorization and Restriction of Chemicals (hereinafter referred to as "REACH") promulgated by the European Union in 2007 stipulates that "environmentally friendly non-toxic materials must be used in the production of lithium-ion batteries"; on the other hand, in the process of recycling waste lithium-ion batteries, it is necessary to avoid waste of resources while effectively reducing pollution to the ecological environment. For example, the European Union promulgated the EU Batteries and Waste Batteries Regulation in 2023, which stipulates that "from 2025, all collected waste batteries must be recycled, and recycling efficiency, material recovery and recycling goals must be gradually implemented, especially key raw materials such as lithium, cobalt, and nickel". Therefore, in the process of making lithium-ion batteries, it is necessary to use healthy, environmentally friendly, non-toxic, and recyclable raw materials as much as possible while ensuring the performance of lithium-ion batteries.

[0003] At present, lithium-ion batteries are mainly composed of positive electrode, negative electrode, separator, electrolyte and shell. As one of the most important components of lithium-ion batteries, positive electrode materials account for 40% to 50% of the overall value of lithium-ion batteries. They are mainly coated on the current collector with a slurry composed of positive electrode active materials, adhesives and conductive agents. Among them, although the proportion of lithium-ion battery adhesives in the manufacturing process of lithium-ion batteries is relatively low (usually accounting for 1% to 5% of the mass of the positive electrode sheet), they are directly related to the adhesion stability between positive electrode active materials, between active materials and conductive agents, and between active materials and current collectors, and directly affect the cycle performance and rate performance of the battery; polyvinylidene fluoride (PVDF) is currently the most widely used positive electrode adhesive in the production process of lithium-ion batteries, but on the one hand, it belongs to perfluorinated and polyfluoroalkyl substances (PFAS), that is, an organic compound containing a high proportion of CF bonds, which will cause harm to human health. On the other hand, polyvinylidene fluoride adhesives are expensive and have weak adhesion to metal current collectors. During the cycle charge and discharge process, they are affected by stress, which will cause the adhesion performance to continue to decline, and then lead to an increase in the impedance between the current collector and the slurry layer, which directly affects the overall performance of the positive electrode sheet. Summary of the invention

[0004] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing an environmentally friendly positive electrode sheet. During the preparation process of the positive electrode sheet, a non-toxic and harmless adhesive is used, and the amount of adhesive used can be effectively reduced, the loading amount of active substances in the electrode can be increased, and the energy density of the battery can be improved; in addition, the electrode sheet prepared by this method can also effectively improve the bonding strength between the positive electrode active substance and the current collector, thereby ensuring the overall performance between the positive electrode sheet and the lithium-ion battery.

[0005] Another object of the present invention is to provide a method for preparing an environmentally friendly lithium-ion battery, which is obtained by using the positive electrode sheet prepared by the above method.

[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing an environmentally friendly positive electrode sheet, comprising: Step A1, adding polyacrylonitrile to NMP solvent, stirring for 2.5 to 3.5 hours to disperse it to form a transparent and uniform solution; Step A2: First, add conductive carbon nanotubes to the transparent and uniform solution in step A1, and stir thoroughly for 0.8 to 1.2 hours at room temperature; then, add conductive carbon black to the solution, and stir thoroughly for 0.8 to 1.2 hours; finally, add positive electrode active material to the solution, and stir for 3.5 to 4.5 hours to obtain a positive electrode slurry with a slurry fineness of less than 40 μm; Step A3: The positive electrode slurry obtained in step A2 is evenly coated on both sides of the positive electrode current collector (double-sided coating ensures that the surface density of each single side is the same), and then dried and rolled to obtain a positive electrode sheet.

[0007] Based on further optimization of the above scheme, in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active materials are: 0.7%~0.9%: 0.45%~0.55%: 0.45%~0.55%: 98%~98.4%; wherein the mass ratio of conductive carbon nanotubes to conductive carbon black is 1:1.

[0008] Based on further optimization of the above scheme, the specific ratio of polyacrylonitrile to NMP solvent in step A is: polyacrylonitrile accounts for 5.5% to 5.7% of the weight of NMP solvent; wherein the molecular weight of polyacrylonitrile is 100 to 150W.

[0009] Based on further optimization of the above scheme, the positive electrode active material in step A2 adopts lithium-cobalt fully-recoverable L917 lithium cobalt oxide.

[0010] Based on the further optimization of the above scheme, the positive electrode current collector in step A3 is aluminum foil; the drying temperature in step A3 is 100-120°C and the drying time is 3.5-4.5h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 4.11-4.13g / cm 3 The product is rolled and immediately slit with a slitting knife and placed in an oven at 100 to 120° C. for 3.5 to 4.5 hours.

[0011] In the process of preparing the positive electrode slurry, the present invention first combines the polyacrylonitrile adhesive with the conductive carbon nanotubes to form a three-dimensional conductive network, and then the nano-bite mechanism of the carbon nanotubes and the adhesive cooperate to effectively improve the bonding ability and electron transmission ability of the positive electrode slurry; after that, conductive carbon black is added, firstly, the three-dimensional conductive network is uniformly filled with conductive carbon black, thereby increasing the electron transmission path, reducing the electron transmission distance, and further increasing the electron transmission ability, and secondly, the three-dimensional network formed first is used as a skeleton structure to guide the conductive carbon black to avoid agglomeration and the distribution of conductive carbon black when adding conductive carbon black, thereby effectively ensuring the uniform transmission of electrons and the uniform adhesion of the positive electrode slurry. In addition, through the polyacrylonitrile adhesive and the specific positive active material, a strong hydrogen bond force and dipole force are formed, thereby further improving the adhesion effect of the positive electrode slurry, reinforcing the stability of the three-dimensional conductive network during the cycle, and increasing the flexibility and mechanical strength of the positive electrode sheet.

[0012] A method for preparing an environmentally friendly lithium-ion battery, comprising: Step B1, positive electrode sheet preparation: obtain a positive electrode sheet by the method described above; Step B2, preparation of negative electrode sheet: first, add thickener to deionized water solvent and stir for 2-3h; then, add conductive agent and stir for 0.4-0.6h, then add graphite and stir thoroughly for 0.8-1.2h to obtain a mixed solution; then, add binder to the mixed solution, stir evenly for 2.3-2.7h to obtain negative electrode slurry; finally, coat the negative electrode slurry evenly on both sides of the negative electrode current collector (double-sided coating ensures that the surface density of each single side is the same), and dry and roll press in sequence to obtain a negative electrode sheet; Step B3, diaphragm preparation and assembly: Use a diaphragm coated with ceramic on one side and PMMA on both sides, model 0.5+5+2+0.5, that is, ceramic on one side and PMMA on both sides; separate the positive electrode sheet and the negative electrode sheet with a 0.5+5+2+0.5 diaphragm, wind them into a soft-pack battery cell, put them into a shell, and dry them; Step B4, electrolyte preparation: Use REACH type electrolyte F35 (4.4V) to inject the electrolyte into the shell of the soft-pack battery cell assembled in step B3, and perform infiltration, sealing, formation, secondary packaging, and capacity division in sequence to obtain a lithium-ion battery.

[0013] The present invention forms a strong hydrogen bonding force by combining a polyacrylonitrile adhesive, a specific conductive agent, a positive electrode active material and a specific diaphragm, thereby enhancing the adhesion between the diaphragm and the positive electrode sheet, reducing the expansion that occurs during the battery cycle (i.e., suppressing the expansion during the battery cycle), and reducing the transmission distance of lithium ions, thereby effectively improving the battery's charge and discharge efficiency and extending the battery's service life.

[0014] Based on further optimization of the above scheme, in the negative electrode slurry of step B2, the mass percentages of thickener, conductive agent, graphite and adhesive are 1.2%-1.4%: 0.9%-1.1%: 95.9%-96.5%: 1.4%-1.6%; wherein the thickener is carboxymethyl cellulose lithium (CMC-Li); the conductive agent is a combination of any one or more of conductive carbon black, conductive graphene and conductive carbon nanotubes; the adhesive is a solution made of styrene-butadiene rubber, and the solvent is a mixed solvent of NMP and deionized water, wherein the mass ratio of styrene-butadiene rubber, NMP and deionized water is: 0.75-0.85: 0.75-0.85: 1; the negative electrode current collector is copper foil.

[0015] Based on further optimization of the above scheme, in step B2, the drying temperature is 90-110° C. and the drying time is 1.5-2.5 h.

[0016] Based on further optimization of the above scheme, in step B3, the outer shell adopts an aluminum-plastic shell; the drying temperature is 75-85° C., and the drying time is 46-50 hours.

[0017] The following are the technical effects of the solution of the present invention: In the positive electrode sheet preparation method provided in the present application, the positive electrode slurry composed of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active materials does not contain any toxic or harmful substances, and meets the current environmental protection requirements of positive electrode sheets of lithium ion batteries; at the same time, the positive electrode slurry improves the bonding strength between the positive electrode active material and the positive electrode collector while reducing the amount of adhesive used through the above-mentioned combined formula and preparation method, ensures uniform and tight adhesion between the positive electrode slurry and the positive electrode collector, effectively increases the loading amount of the active material in the electrode, not only enhances the battery cycle performance between the positive electrode active material and the positive electrode collector, but also improves the energy density of the battery, ensures the uniform transmission of electrons in the battery, and thus improves the overall performance of the battery.

[0018] In the lithium-ion battery preparation method provided in the present application, by cooperating with a specific positive electrode sheet and a diaphragm, not only the stable bonding performance between the diaphragm and the positive electrode sheet is enhanced, but also the potential expansion during the battery cycle is reduced, thereby improving the charging and discharging efficiency and performance of the lithium-ion battery, reducing the damage of the lithium-ion battery due to expansion, and increasing the service life of the lithium-ion battery; in the present application, each raw material is simple and easy to obtain, the production cost is low, and the application range is wide. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a TG test chart of the adhesive prepared in Example 2 of the present invention.

[0020] Figure 2 This is a negative electrode interface diagram of the lithium-ion battery prepared in Example 2 of the present invention after being disassembled at 0°C and 0.5C / 0.5C for 20 times.

[0021] Figure 3 It is a slurry stability test diagram of the embodiment of the present invention and the comparative example.

[0022] Figure 4 The graph is a test diagram of the electrode peeling force of the positive electrode sheets prepared in the embodiments of the present invention and the comparative example.

[0023] Figure 5 The figure is a capacity retention rate diagram of the lithium-ion batteries prepared in the embodiments of the present invention and the comparative examples at 25° C. and 2C / 1.5C charge and discharge for 500 cycles.

[0024] Figure 6 The battery expansion rate diagram of the lithium-ion batteries prepared in the embodiments of the present invention and the comparative examples at 25° C. and 500 cycles of 2C / 1.5C charge and discharge. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0026] Embodiment 1: A method for preparing an environmentally friendly positive electrode sheet, comprising: Step A1, adding polyacrylonitrile to NMP solvent, the specific ratio of polyacrylonitrile to NMP solvent is: polyacrylonitrile accounts for 5.5% of the weight of NMP solvent, the molecular weight of polyacrylonitrile is 100W, stirring for 2.5 hours to disperse it to form a transparent and uniform solution; Step A2. First, add conductive carbon nanotubes to the transparent and uniform solution in step A1 and stir thoroughly for 0.8h at room temperature; then, add conductive carbon black to the solution and stir thoroughly for 0.8h; finally, add positive electrode active material to the solution, the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and stir for 3.5h to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 0.7%: 0.45%: 0.45%: 98.4%.

[0027] Step A3: The positive electrode slurry obtained in step A2 is evenly coated on both sides of the aluminum foil (double-sided coating ensures that the surface density of each side is the same. In this embodiment, the surface density is maintained at 13 mg / cm 2 ), and then drying and rolling in sequence, the drying temperature is 100℃, and the drying time is 4.5h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 4.11g / cm 3 The positive electrode sheet was obtained by rolling and immediately slitting with a slitting knife and placing in an oven at 100°C for 4.5 hours.

[0028] A method for preparing an environmentally friendly lithium-ion battery, comprising: Step B1, positive electrode sheet preparation: obtain a positive electrode sheet by the method described above; Step B2, preparation of negative electrode sheet: First, add thickener to deionized water solvent and stir for 2h; then, add conductive agent and stir for 0.4h, then add graphite and stir thoroughly for 0.8h to obtain a mixed solution; then, add adhesive to the mixed solution, stir evenly for 2.3h to obtain negative electrode slurry; the mass percentages of thickener, conductive agent, graphite and adhesive are 1.2%: 0.9%: 96.5%: 1.4%; wherein, the thickener is carboxymethyl cellulose lithium (CMC-Li); the conductive agent is conductive graphene; the adhesive is a solution made of styrene-butadiene rubber, and the solvent is a mixed solvent composed of NMP and deionized water, wherein the mass ratio of styrene-butadiene rubber, NMP and deionized water is: 0.75: 0.75: 1. Finally, the negative electrode slurry is evenly coated on both sides of the copper foil (double-sided coating ensures that the surface density of each single side is the same. In this embodiment, the surface density is maintained at 7.3mg / cm 2 ), and drying and rolling are performed in sequence, the drying temperature is 90°C, and the drying time is 1.5h, to obtain a negative electrode sheet (rolling can adopt the rolling method of the above-mentioned positive electrode sheet, or other similar methods); Step B3, diaphragm preparation and assembly: Use a diaphragm with ceramic coating on one side and PMMA coating on both sides, model 0.5+5+2+0.5, that is, ceramic coating on one side and PMMA coating on both sides; separate the positive electrode sheet and the negative electrode sheet with a 0.5+5+2+0.5 diaphragm, wind them into a soft-pack battery cell, and put them into an aluminum-plastic shell, and dry them; the drying temperature is 75°C and the drying time is 50h.

[0029] Step B4, electrolyte preparation: Use REACH type electrolyte F35 (4.4V) to inject the electrolyte into the shell equipped with the soft-pack battery cell in step B3, and perform infiltration, sealing, formation, secondary packaging, and capacity division in sequence (wherein, infiltration, sealing, formation, secondary packaging, and capacity division are all conventional means in the art, and are not specifically limited in this embodiment) to obtain a lithium-ion battery.

[0030] It should be noted that, unless otherwise specified in this embodiment, the stirring speed in this embodiment is determined according to actual conditions and only needs to ensure sufficient and uniform stirring.

[0031] Embodiment 2: A method for preparing an environmentally friendly positive electrode sheet, comprising: Step A1, adding polyacrylonitrile to NMP solvent, the specific ratio of polyacrylonitrile to NMP solvent is: polyacrylonitrile accounts for 5.6% of the weight of NMP solvent, the molecular weight of polyacrylonitrile is 125W, and stirring for 3 hours to disperse it to form a transparent and uniform solution; Step A2. First, add conductive carbon nanotubes to the transparent and uniform solution in step A1 and stir thoroughly for 1 hour at room temperature; then, add conductive carbon black to the solution and stir thoroughly for 1 hour; finally, add positive electrode active material to the solution, the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and stir for 4 hours to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 0.8%: 0.5%: 0.5%: 98.2%.

[0032] Step A3: The positive electrode slurry obtained in step A2 is evenly coated on both sides of the aluminum foil (double-sided coating ensures that the surface density of each side is the same. In this embodiment, the surface density is maintained at 14 mg / cm 2 ), and then drying and rolling in sequence, the drying temperature is 110℃, and the drying time is 4h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 4.12g / cm 3 The positive electrode sheet was obtained by rolling and immediately slitting with a slitting knife and placing in an oven at 110° C. for 4 hours.

[0033] The final adhesive was subjected to thermogravimetric analysis (TG) and the resulting curve was as follows: Figure 1 As shown, according to Figure 1 Those skilled in the art will clearly know that the adhesive prepared in this embodiment has excellent thermal stability.

[0034] A method for preparing an environmentally friendly lithium-ion battery, comprising: Step B1, positive electrode sheet preparation: obtain a positive electrode sheet by the method described above; Step B2, preparation of negative electrode sheet: first, add thickener to deionized water solvent and stir for 2.5h; then, add conductive agent and stir for 0.5h, then add graphite and stir thoroughly for 1h to obtain a mixed solution; then, add adhesive to the mixed solution, stir evenly for 2.5h to obtain negative electrode slurry; the mass percentage of thickener, conductive agent, graphite and adhesive is 1.3%:1%:96.2%:1.5%; wherein, the thickener is carboxymethyl cellulose lithium (CMC-Li); the conductive agent is a mixture of conductive carbon black and conductive carbon nanotubes, and the mass ratio of conductive carbon black to conductive carbon nanotubes is 1:1; the adhesive is a solution made of styrene-butadiene rubber, and the solvent is a mixed solvent composed of NMP and deionized water, wherein the mass ratio of styrene-butadiene rubber, NMP and deionized water is: 0.8:0.8:1. Finally, the negative electrode slurry is evenly coated on both sides of the copper foil (double-sided coating ensures that the surface density of each side is the same. In this embodiment, the surface density is maintained at 7.4 mg / cm 2 ), and drying and rolling are performed in sequence, the drying temperature is 100°C, and the drying time is 2h, to obtain a negative electrode sheet (rolling can adopt the rolling method of the positive electrode sheet mentioned above, or other similar methods); Step B3, diaphragm preparation and assembly: Use a diaphragm with ceramic coating on one side and PMMA coating on both sides, model 0.5+5+2+0.5, that is, ceramic coating on one side and PMMA coating on both sides; separate the positive electrode sheet and the negative electrode sheet with a 0.5+5+2+0.5 diaphragm, wind them into a soft-pack battery cell, and put them into an aluminum-plastic shell, and dry them; the drying temperature is 80°C and the drying time is 48h.

[0035] Step B4, electrolyte preparation: Use REACH type electrolyte F35 (4.4V) to inject the electrolyte into the shell equipped with the soft-pack battery cell in step B3, and perform infiltration, sealing, formation, secondary packaging, and capacity division in sequence (wherein, infiltration, sealing, formation, secondary packaging, and capacity division are all conventional means in the art, and are not specifically limited in this embodiment) to obtain a lithium-ion battery.

[0036] It should be noted that, unless otherwise specified in this embodiment, the stirring speed in this embodiment is determined according to actual conditions and only needs to ensure sufficient and uniform stirring.

[0037] The negative electrode interface of the final lithium-ion battery after disassembly after 20 cycles of charge and discharge at 0.5C / 0.5C at 0°C is as follows: Figure 2 As shown, according to Figure 2 Those skilled in the art can clearly see that no lithium deposition occurs after 20 cycles, indicating that the lithium-ion battery prepared in this embodiment has stable performance during continuous charge and discharge.

[0038] Embodiment 3: A method for preparing an environmentally friendly positive electrode sheet, comprising: Step A1, adding polyacrylonitrile to NMP solvent, the specific ratio of polyacrylonitrile to NMP solvent is: polyacrylonitrile accounts for 5.7% of the weight of NMP solvent, the molecular weight of polyacrylonitrile is 150W, stirring for 3.5 hours to disperse it to form a transparent and uniform solution; Step A2. First, add conductive carbon nanotubes to the transparent and uniform solution in step A1 and stir thoroughly for 1.2 hours at room temperature; then, add conductive carbon black to the solution and stir thoroughly for 1.2 hours; finally, add positive electrode active material to the solution, the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and stir for 4.5 hours to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 0.9%: 0.55%: 0.55%: 98%.

[0039] Step A3: The positive electrode slurry obtained in step A2 is evenly coated on both sides of the aluminum foil (double-sided coating ensures that the surface density of each side is the same. In this embodiment, the surface density is maintained at 15 mg / cm 2 ), and then drying and rolling in sequence, the drying temperature is 120℃, and the drying time is 3.5h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 4.13g / cm 3 The positive electrode sheet was obtained by rolling and immediately slitting with a slitting knife and placing in an oven at 120°C for 3.5 hours.

[0040] A method for preparing an environmentally friendly lithium-ion battery, comprising: Step B1, positive electrode sheet preparation: obtain a positive electrode sheet by the method described above; Step B2, preparation of negative electrode sheet: First, add thickener to deionized water solvent and stir for 3 hours; then, add conductive agent and stir for 0.6 hours, then add graphite and stir thoroughly for 1.2 hours to obtain a mixed solution; then, add adhesive to the mixed solution and stir evenly for 2.7 hours to obtain negative electrode slurry; the mass percentages of thickener, conductive agent, graphite and adhesive are 1.4%: 1.1%: 95.9%: 1.6%; wherein, the thickener is carboxymethyl cellulose lithium (CMC-Li); the conductive agent is conductive carbon nanotubes; the adhesive is a solution made of styrene-butadiene rubber, and the solvent is a mixed solvent composed of NMP and deionized water, wherein the mass ratio of styrene-butadiene rubber, NMP and deionized water is: 0.85: 0.85: 1. Finally, the negative electrode slurry is evenly coated on both sides of the copper foil (double-sided coating ensures that the surface density of each single side is the same. In this embodiment, the surface density is maintained at 7.5 mg / cm 2 ), and drying and rolling are performed in sequence, the drying temperature is 110°C, and the drying time is 2.5h, to obtain a negative electrode sheet (rolling can adopt the rolling method of the positive electrode sheet mentioned above, or other similar methods); Step B3, diaphragm preparation and assembly: Use a diaphragm with ceramic coating on one side and PMMA coating on both sides, model 0.5+5+2+0.5, that is, ceramic coating on one side and PMMA coating on both sides; separate the positive electrode sheet and the negative electrode sheet with a 0.5+5+2+0.5 diaphragm, wind them into a soft-pack battery cell, and put them into an aluminum-plastic shell, and dry them; the drying temperature is 85°C and the drying time is 46h.

[0041] Step B4, electrolyte preparation: Use REACH type electrolyte F35 (4.4V) to inject the electrolyte into the shell equipped with the soft-pack battery cell in step B3, and perform infiltration, sealing, formation, secondary packaging, and capacity division in sequence (wherein, infiltration, sealing, formation, secondary packaging, and capacity division are all conventional means in the art, and are not specifically limited in this embodiment) to obtain a lithium-ion battery.

[0042] It should be noted that: unless otherwise specified in this embodiment, the stirring speed in this embodiment is determined according to actual conditions and only needs to ensure sufficient and uniform stirring.

[0043] Comparative Example 1: A method for preparing a positive electrode sheet, comprising: Step A1: This step is consistent with step A1 in Example 2; Step A2. First, add conductive carbon black to the transparent and uniform solution in step A1 and stir it thoroughly at room temperature for 1 hour; then, add conductive carbon nanotubes to the solution and stir it thoroughly for 1 hour; finally, add positive electrode active material to the solution, the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and stir it for 4 hours to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 0.8%: 0.5%: 0.5%: 98.2%.

[0044] Step A3: This step is consistent with step A3 in Example 2.

[0045] A method for preparing a lithium ion battery, comprising: Step B1, positive electrode sheet preparation: obtain a positive electrode sheet by the method described above; Step B2, preparation of negative electrode sheet: the same as step B2 in Example 2; Step B3, diaphragm preparation and assembly: consistent with step B3 in Example 2.

[0046] Step B4, electrolyte preparation: the same as step B4 in Example 2.

[0047] Comparative Example 2: A method for preparing a positive electrode sheet, comprising: Step A1: This step is consistent with step A1 in Example 2; Step A2. First, add conductive carbon nanotubes to the transparent and uniform solution in step A1 and stir thoroughly for 1 hour at room temperature; then, add conductive carbon black to the solution and stir thoroughly for 1 hour; finally, add positive electrode active material to the solution, the positive electrode active material is nickel cobalt manganese oxide NCM622, and stir for 4 hours to obtain a positive electrode slurry with a slurry fineness of less than 40 μm; in the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 0.8%: 0.5%: 0.5%: 98.2%.

[0048] Step A3: This step is to adjust the compaction density to 3.6 g / cm 3 The remaining steps are consistent with step A3 in Example 2.

[0049] A method for preparing a lithium ion battery, comprising: Step B1, positive electrode sheet preparation: obtain a positive electrode sheet by the method described above; Step B2, preparation of negative electrode sheet: the same as step B2 in Example 2; Step B3, diaphragm preparation and assembly: consistent with step B3 in Example 2.

[0050] Step B4, electrolyte preparation: the same as step B4 in Example 2.

[0051] Comparative Example 3: A method for preparing a positive electrode sheet, comprising: Step A1, adding polyvinylidene fluoride (PVDF) into NMP solvent, the mass ratio of polyvinylidene fluoride to NMP solvent is 56:100, and stirring for 3 hours to disperse it to form a uniform solution; Step A2. First, add conductive carbon nanotubes to the transparent and uniform solution in step A1 and stir thoroughly for 1 hour at room temperature; then, add conductive carbon black to the solution and stir thoroughly for 1 hour; finally, add positive electrode active material to the solution, the positive electrode active material adopts lithium cobalt fully recovered L917 lithium cobalt oxide, and stir for 4 hours to obtain a positive electrode slurry with a slurry fineness of less than 40μm; in the positive electrode slurry, the mass percentages of polyvinylidene fluoride, conductive carbon nanotubes, conductive carbon black and positive electrode active material are: 1.0%: 0.5%: 0.5%: 98%.

[0052] Step A3: This step is consistent with step A3 in Example 2.

[0053] A method for preparing a lithium ion battery, comprising: Step B1, positive electrode sheet preparation: obtain a positive electrode sheet by the method described above; Step B2, preparation of negative electrode sheet: the same as step B2 in Example 2; Step B3, diaphragm preparation and assembly: consistent with step B3 in Example 2.

[0054] Step B4, electrolyte preparation: the same as step B4 in Example 2.

[0055] Comparative Example 4: A method for preparing a lithium ion battery, comprising: Step B1, preparing a positive electrode sheet: preparing a positive electrode sheet through steps A1 to A3 in Example 2; Step B2, preparation of negative electrode sheet: the same as step B2 in Example 2; Step B3, diaphragm preparation and assembly: Use conventional PVDF-coated diaphragm in the art, model 5+2+2; separate the above positive and negative plates with 5+2+2 diaphragm and wind them into bare cells, put them into aluminum-plastic shells, and dry them; the drying temperature is 80°C and the drying time is 48h.

[0056] Step B4, electrolyte preparation: the same as step B4 in Example 2.

[0057] The changes in the solid content of the positive electrode slurry in Examples 1 to 3 and Comparative Examples 1 to 4 are as follows: Figure 3 As shown by Figure 3It can be clearly seen that the solid content in Comparative Examples 1 and 2 shows a significant downward trend in the later stage of the test, and the solid content stability is poor, which is mainly caused by the change in the addition sequence of the positive electrode active material and the conductive agent and the combination of the binder.

[0058] The electrode peeling force test diagrams of Examples 1 to 3 and Comparative Examples 1 to 4 are shown in FIG. Figure 4 As shown, it can be clearly seen that the electrode sheet prepared by the method of the present application has stronger peeling force and is more stable; the capacity retention rate of 500 cycles of charge and discharge in Examples 1 to 3 and Comparative Examples 1 to 4 is as follows Figure 5 As shown: the retention rate in Example 2 of the present application is the highest, the retention rate in Comparative Example 1 is the lowest, and Comparative Example 2 is the second lowest; the battery expansion rate of 500 charge and discharge cycles in Examples 1 to 3 and Comparative Examples 1 to 4 is as shown Figure 6 As shown: Example 2 has the lowest expansion rate, Comparative Example 1 has the highest expansion rate, and Comparative Example 2 has the second highest expansion rate, which proves that the order of adding the conductive agent and the selection of the positive electrode active material in combination with the specific adhesive can effectively improve the adhesion of the electrode sheet and the capacity retention rate after charging and discharging, and reduce the battery expansion rate during charging and discharging.

Claims

1. A method for preparing an environmentally friendly positive electrode sheet, characterized in that: include: Step A1, adding polyacrylonitrile to NMP solvent, stirring for 2.5 to 3.5 hours to disperse it to form a transparent and uniform solution; Step A2: First, add conductive carbon nanotubes to the transparent and uniform solution in step A1, and stir thoroughly for 0.8 to 1.2 hours at room temperature; then, add conductive carbon black to the solution, and stir thoroughly for 0.8 to 1.2 hours; finally, add positive electrode active material to the solution, and stir for 3.5 to 4.5 hours to obtain a positive electrode slurry with a slurry fineness of less than 40 μm; Step A3: coating the positive electrode slurry obtained in step A2 evenly on both sides of the positive electrode current collector, and drying and rolling the positive electrode slurry in sequence to obtain a positive electrode sheet.

2. The method for preparing an environmentally friendly positive electrode sheet according to claim 1, characterized in that: In the positive electrode slurry, the mass percentages of polyacrylonitrile, conductive carbon nanotubes, conductive carbon black and positive electrode active materials are: 0.7%-0.9%: 0.45%-0.55%: 0.45%-0.55%: 98%-98.4%; wherein the mass ratio of conductive carbon nanotubes to conductive carbon black is 1:

1.

3. A method for preparing an environmentally friendly positive electrode sheet according to claim 1 or 2, characterized in that: The specific ratio of polyacrylonitrile to NMP solvent in step A is: polyacrylonitrile accounts for 5.5% to 5.7% of the weight of NMP solvent; wherein the molecular weight of polyacrylonitrile is 100 to 150W.

4. The method for preparing an environmentally friendly positive electrode sheet according to claim 3, characterized in that: In the step A2, the positive electrode active material is L917 lithium cobalt oxide which is a fully recycled type of lithium and cobalt.

5. The method for preparing an environmentally friendly positive electrode sheet according to claim 3, characterized in that: The positive electrode current collector in step A3 is aluminum foil; the drying temperature in step A3 is 100-120°C and the drying time is 3.5-4.5h; the rolling process is specifically as follows: adjusting the roller press so that the compaction density is maintained at 4.11-4.13g / cm 3 The product is rolled and immediately slit with a slitting knife and placed in an oven at 100 to 120° C. for 3.5 to 4.5 hours.

6. A method for preparing an environmentally friendly lithium-ion battery, using the positive electrode sheet prepared as claimed in any one of claims 1 to 5, characterized in that: include: Step B1, preparing the positive electrode sheet; Step B2, negative electrode sheet preparation: First, add the thickener into the deionized water solvent and stir for 2 to 3 hours; Then, a conductive agent is added and stirred for 0.4 to 0.6 hours, and then graphite is added and stirred for 0.8 to 1.2 hours to obtain a mixed solution; then, a binder is added to the mixed solution, and stirred evenly for 2.3 to 2.7 hours to obtain a negative electrode slurry; finally, the negative electrode slurry is evenly coated on both sides of the negative electrode current collector, and dried and rolled in sequence to obtain a negative electrode sheet; Step B3, diaphragm preparation and assembly: Use a diaphragm coated with ceramic on one side and PMMA on both sides, model 0.5+5+2+0.5, that is, ceramic on one side and PMMA on both sides; separate the positive electrode sheet and the negative electrode sheet with a 0.5+5+2+0.5 diaphragm, wind them into a soft-pack battery cell, put them into a shell, and dry them; Step B4, electrolyte preparation: Use REACH type electrolyte F35 to inject the electrolyte into the shell equipped with the soft-pack battery cell in step B3, and perform infiltration, sealing, formation, secondary packaging, and capacity division in sequence to obtain a lithium-ion battery.

7. The method for preparing an environmentally friendly lithium-ion battery according to claim 6, characterized in that: In the negative electrode slurry of step B2, the mass percentages of thickener, conductive agent, graphite and adhesive are 1.2% to 1.4%: 0.9% to 1.1%: 95.9% to 96.5%: 1.4% to 1.6%; wherein the thickener is lithium carboxymethyl cellulose; the conductive agent is a combination of any one or more of conductive carbon black, conductive graphene and conductive carbon nanotubes; the adhesive is a solution made of styrene-butadiene rubber, and the solvent is a mixed solvent composed of NMP and deionized water, wherein the mass ratio of styrene-butadiene rubber, NMP and deionized water is: 0.75~0.85:0.75~0.85:1; the negative electrode current collector is made of copper foil.